(untitled) (Research, Society and Development, 2021)
Objective: analyze information on how the coronavirus emerges as one of the great uncertainties in the economic scenario in 2020. The impacto on the world economy and what are the new projections for the coming months. The factors and risks perceived by globalization, as well as the scenarios for the evolution of trade worldwide, such as this global crisis that we are currently experiencing. Methodology: This is a bibliographic study, the analysis and gathering of information was based on articles already published about the coronavirus on the world scene to date. Everything we have shown has been adapted and compiled as necessary to understand the current situation regarding foreign trade. Conclusion: With this bibliographic study, the impact on foreign trade resulting from a health situation in which we have not experienced anything similar in the last 100 years was perceived. What are our expectations and projections expected for the next year and what were the losses to date time.